Impact of Wash Oil Composition on Degradation: A Comparative Analysis of “Light” and “Heavy” Oils - Denis Miroshnichenko; Artem Bannikov; Leonid Bannikov; Olexandr Borisenko; Andrei Shishkin; Pavels Gavrilovs; Volodymyr Tertychnyi (Resources)
This study aims to address the limited understanding of wash oil degradation in benzene units by analysing changes in the composition and properties of fresh and operating oils from different manufacturers. The findings will provide insights into the degradation pathways and stability of these oils. Gas chromatography/mass spectrometry was used to analyse the provided samples, and the dynamic viscosity of the oils was determined using a Brookfield LV DV2T rotational viscometer. During operation, the “heavy” oil (HO) becomes less volatile, while the ”light” oil (LO) becomes slightly more volatile. The viscosity of the HO increases 1.25 times during operation. The LO is characterised by a higher total concentration of alkyl derivatives (48 wt.% compared to 44 wt.% for the HO). LO is enriched with naphthalene and indene, while HO loses 1- and 2-methylnaphthalenes and shows an increase in the concentrations of dibenzofuran, fluorene, anthracene, and phenanthrene. The oxidation products of LO include oxidised alkyl groups, while HO shows oxidised non-substituted hydrocarbons. The practical value of such studies lies in guiding the selection of fresh oil under current operating conditions. LO is more resistant to degradation as an absorbent than heavier wash oil.